The Influence of Instagram Celebrity Endorsement on Purchase Intention of Erigo Products - Ferdyan Ilhaam Saputro; Budi Astuti (International Journal of Economics, Business and Innovation Research, 2024)
One of the marketing strategies related to social media is the celebrity endorsement strategy. However, there is one aspect that needs to be considered for a business when implementing a marketing strategy in the form of celebrity endorsement, namely the celebrity aspect. This study aims to analyze and examine the influence of celebrity aspects including trustworthiness, product match-up, and attractiveness in triggering purchase intentions with consumer perceptions as a mediator. This study uses a quantitative approach method by distributing questionnaires to 165 respondents of Instagram social media users who know the Erigo fashion brand and know Angga Yunanda as a celebrity endorser. The results of data collection were statistically analyzed using PLS-SEM with SmartPLS software. The results prove that celebrity aspects including trustworthiness, product match-up, and attractiveness have a positive and significant influence on consumer perceptions through Instagram celebrity endorsements. In addition, consumer perception can act as a mediator in the relationship between product match-up and consumer purchase intention. This study also reveals that consumer perceptions can have a positive and significant effect on purchase intentions